Serum amyloid A 1 induces suppressive neutrophils through the Toll‐like receptor 2–mediated signaling pathway to promote progression of breast cancer. Issue 4 (13th February 2022) - Niu, Xingjian; Yin, Lei; Yang, Xudong; Yang, Yue; Gu, Yucui; Sun, Yutian; Yang, Ming; Wang, Yiran; Zhang, Qingyuan; Ji, Hongfei
Abstract: Immune inflammation plays a key role in breast cancer development, progression, and therapeutic efficacy. Neutrophils are crucial for the regulation of the suppressive tumor microenvironment and are associated with poor clinical survival. However, the mechanisms underlying the activation of suppressive neutrophils in breast cancer are poorly understood. Here, we report that breast cancer cells secrete abundant serum amyloid A 1 (SAA1), which is associated with the accumulation of suppressive neutrophils. High expression of SAA1 in breast cancer induces neutrophil immunosuppressive cytokine production through the activation of Toll‐like receptor 2 (TLR2)‐mediated signaling pathways. These include the TLR2/myeloid differentiation primary response 88 (MYD88)‐mediated PI3K/nuclear factor‐κB signaling pathway and p38 MAPK‐associated apoptosis resistance pathway, which eventually promote the progression of breast cancer. Our study shows a mechanistic link between breast cancer cell secretion of SAA1 and suppressive neutrophils that potentiate tumor progression. These findings provide potential therapeutic targets for breast cancer. Abstract : Our study shows a mechanistic link between breast cancer cell secretion of serum amyloid A 1 and suppressive neutrophils that potentiate tumor progression. These findings provide potential therapeutic targets for breast cancer.